The morphology of the Milky Way – I. Reconstructing CO maps from simulations in fixed potentials - Pettitt, Alex R.; Dobbs, Clare L.; Acreman, David M.; Price, Daniel J. (Monthly notices of the Royal Astronomical Society, 2014)
We present an investigation into the morphological features of the Milky Way. We use smoothed particle hydrodynamics (SPH) to simulate the interstellar medium (ISM) in the Milky Way under the effect of a number of different gravitational potentials representing spiral arms and bars, assuming that the Milky Way is a grand design spiral in nature. The gas is subject to ISM cooling and chemistry, enabling us to track the evolution of molecular gas. We use a 3D radiative transfer code to simulate the emission from the SPH output, allowing for the construction of synthetic longitude–velocity (l–v) emission maps as viewed from the Earth. By comparing these maps with the observed emission in CO from the Milky Way, we infer the arm/bar geometry that provides a best fit to our Galaxy. We find that it is possible to reproduce nearly all features of the l–v diagram in CO emission. There is no model, however, that satisfactorily reproduces all of the features simultaneously. Models with two arms cannot reproduce all the observed arm features, while four armed models produce too bright local emission in the inner Galaxy. Our best-fitting models favour a bar pattern speed within 50–60 km s−1 kpc−1 and an arm pattern speed of approximately 20 km s−1 kpc−1, with a bar orientation of approximately 45° and arm pitch angle between 10°–15°.